Low hydrogen permeable structure and manufacturing method thereof

The chromium-containing iron-based material with carbon-hydrogen bonds and an aluminum nitride film addresses shape limitations in hydrogen barrier surfaces, enhancing hydrogen barrier properties and adhesion, suitable for complex objects.

JP7613215B2Active Publication Date: 2025-01-15DENSO CORP +2
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021063498
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-04-02
Publication Date
2025-01-15
Estimated Expiration
2041-04-02

AI Technical Summary

Technical Problem

Existing methods for creating hydrogen barrier surfaces on stainless steel require a counter electrode, limiting the ability to process objects with complex shapes due to shape matching constraints.

Method used

A low hydrogen permeability structure is achieved by using a chromium-containing iron-based material with a quaternary ammonium hydroxide treatment to introduce carbon-hydrogen bonds on the surface, followed by forming an aluminum nitride film using atomic layer deposition.

Benefits of technology

This method allows for excellent hydrogen barrier properties while relaxing shape restrictions, enabling processing of complex objects and improving adhesion between the base material and the film, thereby reducing hydrogen permeability by up to 1/10.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007613215000001
    Figure 0007613215000001
  • Figure 0007613215000002
    Figure 0007613215000002
  • Figure 0007613215000003
    Figure 0007613215000003
Patent Text Reader

Abstract

To provide a low hydrogen permeable structure capable of achieving excellent low hydrogen permeability while relaxing a limit to a product shape and using a chromium containing iron-based material as a base material, and a method for manufacturing the same.SOLUTION: The outermost surface (21) of a base material in a low hydrogen permeable structure (1) using a chromium containing iron-based material as a base material (2) has a carbon-hydrogen bond. The carbon-hydrogen bond on the outermost surface of the base material is introduced by processing the base material by an alkaline medical solution; and a thin film having the carbon-hydrogen bond and formed on the outermost surface of the base material includes at least one of a titanium oxide film, an aluminum oxide film and an aluminum nitride film.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a low hydrogen permeable structure having a base material made of an iron-based material containing chromium, and a method for producing the same. [Background technology]

[0002] Patent Document 1 discloses stainless steel with hydrogen barrier function, in which the stainless steel surface has been electrolytically polished and is coated with a passivated film. Patent Document 1 also discloses a method for producing stainless steel with hydrogen barrier function as described above. This production method is as follows. After electrolytic polishing of the stainless steel surface, a chromium oxide film is formed by anodic electrolysis in a treatment solution consisting of a mixed solution of chromic acid and sulfuric acid, the chromium oxide film is hardened by cathodic electrolysis in a treatment solution consisting of a mixed solution of chromic acid and phosphoric acid, and then the stainless steel is immersed in nitric acid to form a passivated film. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2018-188728 A Summary of the Invention [Problem to be solved by the invention]

[0004] In the technology described in Patent Document 1, a counter electrode is required when electrolytically polishing the stainless steel surface. A certain gap must be provided between the surface of the object to be treated and the surface of the counter electrode. For this reason, it is necessary to process the shape of the counter electrode in accordance with the shape of the object to be treated. In addition, there are limitations to the shapes of objects that can be processed. In other words, it is difficult to apply this technology to objects with complex shapes.

[0005] The present invention has been made in consideration of the above-mentioned circumstances, etc. That is, the present invention provides, for example, a low hydrogen permeable structure having a base material made of an iron-based material containing chromium, which can realize excellent low hydrogen permeability while easing restrictions on the product shape, and a method for manufacturing the same. [Means for solving the problem]

[0006] The low hydrogen permeable structure (1) according to claim 1 has a substrate (2) made of an iron-based material containing chromium, and the substrate has an outermost surface (21) is due to quaternary ammonium Carbon-hydrogen bond is introduced, and a coating film (3) having an aluminum nitride film is formed on the outermost surface. . Claim to 4 The method for producing the low hydrogen permeable structure (1) described above includes the steps of: A substrate (2) made of an iron-based material containing chromium It is a solution of quaternary ammonium hydroxide. By treating with an alkaline chemical solution, the outermost surface (21) of the substrate is Caused by quaternary ammonium hydroxide A step of introducing carbon-hydrogen bonds and, and forming a coating film (3) having an aluminum nitride film on the outermost surface of the substrate into which carbon-hydrogen bonds resulting from a quaternary ammonium hydroxide have been introduced. include.

[0007] In addition, in each section of the application documents, each element may be given a reference symbol in parentheses. In this case, the reference symbol merely indicates an example of the correspondence between the element and the specific configuration described in the embodiment described later. Therefore, the present invention is not limited in any way by the description of the reference symbol. [Brief description of the drawings]

[0008] [Figure 1] 1 is a cross-sectional view showing a schematic configuration of a low hydrogen permeable structure according to one embodiment of the present invention. [Figure 2A] 2A to 2C are cross-sectional views that roughly show a process for producing the low hydrogen permeable structure shown in FIG. [Figure 2B] 2A to 2C are cross-sectional views that roughly show a process for producing the low hydrogen permeable structure shown in FIG. [Figure 3A] 3 is a graph showing the evaluation results of hydrogen permeability in the substrates shown in FIGS. 2A and 2B. [Figure 3B] FIG. 3 is a graph showing the Fe2p spectrum by X-ray photoelectron spectroscopy of the substrate shown in FIG. 2A and FIG. 2B. [Figure 3C] 2C is a graph showing the X-ray photoelectron spectroscopy C1s spectrum of the substrate shown in FIG. 2A and FIG. 2B. [Figure 4] 2 is a graph showing the evaluation results of hydrogen permeability in the low hydrogen permeable structure shown in FIG. [Diagram 5] 2 is a graph showing the evaluation results of hydrogen permeability in the low hydrogen permeable structure shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] (Embodiment) Hereinafter, an embodiment of the present invention will be described with reference to the drawings. Note that, if various modified examples applicable to one embodiment are inserted in the middle of a series of explanations related to the embodiment, it may hinder understanding of the embodiment. For this reason, the modified examples are not inserted in the middle of a series of explanations related to the embodiment, but are explained together after the series of explanations.

[0010] (composition) Referring to FIG. 1, the low hydrogen permeable structure 1 according to this embodiment includes a substrate 2 and a thin film 3. That is, the low hydrogen permeable structure 1 has a structure like a bonded body of the substrate 2 and the thin film 3. The substrate 2 is formed of an iron-based material containing chromium, that is, stainless steel. The thin film 3 has a titanium oxide film, an aluminum oxide film, or an aluminum nitride film. Specifically, the thin film 3 may be formed of, for example, a single layer of aluminum oxide film. Alternatively, the thin film 3 may be formed of, for example, a single layer of titanium oxide film. Alternatively, the thin film 3 may be formed of, for example, a single layer of aluminum nitride film. Alternatively, the thin film 3 may be formed of, for example, a laminated film in which an aluminum oxide film and a titanium oxide film are alternately laminated. Alternatively, the thin film 3 may be formed of, for example, a laminated film in which an aluminum nitride film and a titanium oxide film are alternately laminated.

[0011] The thin film 3 is bonded to the outermost surface 21 of the substrate 2. The outermost surface 21 of the substrate 2 has carbon-hydrogen bonds. That is, the substrate 2 is provided with an outermost layer 22 having carbon-hydrogen bonds. The amount of carbon-hydrogen bonds introduced into the outermost surface 21 of the substrate 2 is expressed by the peak intensity ratio R 285 / 288 In other words, R 285 / 288 It is preferable that the peak intensity ratio R is ≧8. 285 / 288 is the ratio of the peak with bond energy of 285 eV corresponding to a carbon-hydrogen bond in the C1s spectrum by X-ray photoelectron spectroscopy to the peak with bond energy of 288 eV corresponding to a carbon-oxygen bond derived from organic matter that may remain on the outermost surface 21 of the substrate 2.

[0012] (Manufacturing method) An outline of a method for producing the low hydrogen permeable structure 1 having the configuration shown in FIG. 1 will be described with reference to FIGS. 2A and 2B.

[0013] First, as shown in FIG. 2A, a substrate 2 made of an iron-based material containing chromium is prepared. The prepared substrate 2 is degreased with an organic solvent such as acetone, and then the outermost surface 21 of the substrate 2 is treated with an alkaline chemical solution. By such alkaline chemical solution treatment, carbon-hydrogen bonds can be introduced into the outermost surface 21 of the substrate 2, as shown in FIG. 2B. As the alkaline chemical solution, a solution of a quaternary ammonium hydroxide is preferably used. Specific examples of quaternary ammonium hydroxides that can be used include tetramethylammonium hydroxide (i.e., TMAH), tetraethylammonium hydroxide (i.e., TEAH), tetrapropylammonium hydroxide, etc., and TMAH is particularly preferably used. Note that one or more types of quaternary ammonium hydroxide can be used.

[0014] A thin film 3 is formed on the outermost surface 21 of the substrate 2 shown in Fig. 2B by a vapor phase deposition method (for example, ALD), thereby obtaining the low hydrogen permeable structure 1 shown in Fig. 1. ALD is an abbreviation for atomic layer deposition.

[0015] FIG. 3 shows the effect of improving low hydrogen permeability by alkaline chemical treatment on the outermost surface 21 of the substrate 2 made of SUS316L. In the figure, "before treatment" shows the state before the alkaline chemical treatment, i.e., the structure of FIG. 2A, and "after treatment" shows the state after the alkaline chemical treatment, i.e., the structure of FIG. 2B. The alkaline chemical treatment was performed using a 25 wt % aqueous solution of TMAH, and the treatment conditions were 90° C. and 2 minutes. As shown in FIG. 3A, by performing alkaline chemical treatment on the outermost surface 21 of the substrate 2, the hydrogen permeability coefficient was reduced to about 1 / 20.

[0016] To investigate the reason for this, the outermost surface 21 of the substrate 2 was analyzed by X-ray photoelectron spectroscopy. The results are shown in Figures 3B and 3C. Figure 3B shows the Fe2p spectrum, and Figure 3C shows the C1s spectrum. In the figures, the dotted line corresponds to "before treatment" and the solid line corresponds to "after treatment."

[0017] As shown in Figure 3B, the peak at around 711 eV corresponding to iron oxide in the Fe2p spectrum was significantly reduced by the alkaline chemical treatment, while a prominent peak corresponding to carbon-hydrogen bonds appeared in the C1s spectrum of the sample after the alkaline chemical treatment, as shown in Figure 3C.

[0018] These spectra show that the structure of the outermost surface 21 of the substrate 2 is changed from an iron-oxygen bond structure to a carbon-hydrogen bond structure by the alkaline chemical treatment. In other words, the oxygen atoms that form iron oxide (Fe2O3) with the iron atoms present on or near the outermost surface 21 of the substrate 2 are converted by the alkaline chemical treatment into organic molecular ions (CH3)4N having carbon-hydrogen bonds originating from TMAH. + It is believed that the adsorption of the methyl group causes the methyl group to be introduced onto the outermost surface 21 of the substrate 2.

[0019] More specifically, as shown in Figure 3C, in the C1s spectrum of the sample before alkaline chemical treatment, a 285 eV peak corresponding to a carbon-hydrogen bond and a 288 eV peak derived from organic matter were clearly generated. In contrast, in the C1s spectrum of the sample after alkaline chemical treatment, the intensity of the 285 eV peak corresponding to a carbon-hydrogen bond increased significantly, and the 288 eV peak derived from organic matter decreased to a level where it was barely discernible above the noise level. Here, tetramethylammonium ion (CH3)4N + does not have a carbon-oxygen bond corresponding to the 288 eV peak. Therefore, it is considered that the 285 eV peak in the C1s spectrum of the sample before the alkaline chemical treatment is also derived from the same organic matter as the organic matter corresponding to the 288 eV peak. In contrast, the 285 eV peak in the C1s spectrum of the sample after the alkaline chemical treatment is derived from the tetramethylammonium ion (CH3)4N + It is believed that this is due to the methyl group in the peak intensity ratio R 285 / 288 was 1.8 before treatment and 8.3 after treatment.

[0020] 4 and 5 show the effect of improving low hydrogen permeability by forming a thin film 3 on the outermost surface 21 of the substrate 2 after the alkaline chemical solution treatment. In the figures, "film type" indicates the type and structure of the film constituting the thin film 3, and "none" corresponds to the outermost surface 21 of the substrate 2 having only been subjected to an alkaline chemical solution treatment (i.e., before the formation of the thin film 3).

[0021] 4 and 5, the addition of the thin film 3 reduced the hydrogen permeability coefficient by approximately 1 / 10 or more. The reason for this is considered below. By introducing carbon-hydrogen bonds into the outermost surface 21 of the substrate 2, the thin film 3, which is an ALD film, becomes easier to form. Furthermore, the adhesion between the substrate 2 and the thin film 3 improves, which leads to low hydrogen permeability, i.e., improved hydrogen barrier properties.

[0022] Thus, in this embodiment, by performing alkaline chemical treatment instead of electrolytic polishing, restrictions on the shape of the object to be treated are effectively alleviated. Specifically, application to objects having complex shapes is possible. Therefore, according to this embodiment, it is possible to provide a low hydrogen permeable structure 1 and a manufacturing method thereof, which are based on an iron-based material containing chromium and can realize excellent low hydrogen permeability while alleviating restrictions on the product shape. In addition, the adhesion between the base material 2 and the thin film 3 can be improved, thereby improving the low hydrogen permeability, i.e., hydrogen barrier properties, of the low hydrogen permeable structure 1.

[0023] (Modification) The present invention is not limited to the above embodiment. Therefore, the above embodiment can be modified as appropriate. Representative modified examples will be described below. In the following description of the modified examples, differences from the above embodiment will be mainly described. In addition, the same reference numerals are used for parts that are the same or equivalent to each other in the above embodiment and the modified examples. Therefore, in the following description of the modified examples, the description of the above embodiment can be appropriately used for components having the same reference numerals as the above embodiment, unless there is a technical contradiction or special additional explanation.

[0024] In the above embodiment, the effect of improving the degree of freedom of the product shape by performing alkaline chemical treatment instead of electrolytic polishing has been described. However, the present invention is not limited to such a description. That is, for example, when the product shape is relatively simple and electrolytic polishing is possible, the low hydrogen permeability, i.e., the hydrogen barrier property, of the low hydrogen permeable structure 1 can be improved by performing alkaline chemical treatment after electrolytic polishing.

[0025] The method for forming the thin film 3 is not limited to ALD, and general physical vapor deposition or chemical vapor deposition can be used. There are also no particular limitations on the type of film, the number of layers, and the like.

[0026] Needless to say, the elements constituting the above-mentioned embodiment are not necessarily essential, except when expressly stated as essential or when considered to be obviously essential in principle. Furthermore, when the numbers, amounts, ranges, etc. of the components are mentioned, the present invention is not limited to the specific values, except when expressly stated as essential or when clearly limited to a specific value in principle. Similarly, when the shapes, directions, positional relationships, etc. of the components are mentioned, the present invention is not limited to the shapes, directions, positional relationships, etc., except when expressly stated as essential or when clearly limited to a specific shape, direction, positional relationship, etc. in principle.

[0027] The modified examples are not limited to the above examples. That is, for example, other than those exemplified above, multiple embodiments may be combined with each other as long as there is no technical contradiction. Similarly, multiple modified examples may be combined with each other as long as there is no technical contradiction. [Explanation of symbols]

[0028] 1. Low hydrogen permeability structure 2 Base material 21 Top surface 3. Thin Film

Claims

1. A low hydrogen permeable structure (1) having a substrate (2) made of an iron-based material containing chromium, A carbon-hydrogen bond resulting from a quaternary ammonium is introduced into the outermost surface (21) of the substrate, A coating film (3) having an aluminum nitride film is formed on the outermost surface. Low hydrogen permeability structure.

2. The coating film has a titanium oxide film. The low hydrogen permeable structure according to claim 1 .

3. The coating film has an aluminum oxide film. The low hydrogen permeable structure according to claim 1 or 2.

4. A method for producing a low hydrogen permeable structure (1) having a substrate (2) made of an iron-based material containing chromium, comprising the steps of: The substrate is treated with an alkaline chemical solution, which is a solution of a quaternary ammonium hydroxide, to introduce carbon-hydrogen bonds resulting from the quaternary ammonium hydroxide into the outermost surface (21) of the substrate; forming a coating film (3) having an aluminum nitride film on the outermost surface of the substrate into which carbon-hydrogen bonds resulting from a quaternary ammonium hydroxide have been introduced; A method for producing a low hydrogen permeable structure.

5. The coating film has a titanium oxide film. A method for producing the low hydrogen permeable structure according to claim 4.

6. The coating film has an aluminum oxide film. A method for producing the low hydrogen permeable structure according to claim 4 or 5.

7. The coating film is formed by a vapor phase growth method. A method for producing the low hydrogen permeable structure according to any one of claims 4 to 6.

Citation Information

Patent Citations

  • Hydrogen barrier-coated article for stainless steel pipe, vessel or the like, and production method therefor

    JP2005226107A

  • Hydrogen barrier coated article in stainless steel pipe and containers, and its manufacturing method

    JP2007009276A

  • Stainless steel having hydrogen barrier capability and method for producing the same

    JP2018188728A

  • Surface coated member and manufacturing method thereof

    JP2019206741A

  • Laminated coating layer, method for manufacturing same, and method for determining laminated structure

    WO2020129878A1